2020
DOI: 10.1186/s12913-020-05779-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring preference for, and uptake of, rural medical internships, a key issue for supporting rural training pathways

Abstract: Background Improved medical care access for rural populations continues to be a major concern. There remains little published evidence about postgraduate rural pathways of junior doctors, which may have strong implications for a long-term skilled rural workforce. This exploratory study describes and compares preferences for, and uptake of, rural internships by new domestic and international graduates of Victorian medical schools during a period of rural internship position expansion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Studies identified a range of challenges related to classifying the geographical distribution of medical workforce, which were as follows: uptake of rural internships by domestic graduates being insufficient to meet rural workforce demands [76]; movement of graduates who were international fee-paying students to metropolitan areas after the first few years of practice [82]; and the lack of availability of specialty training in non-metropolitan areas [57]. The sensitivity of AHPRA principal place of practice data was also examined in one study, which found that the most accurate method of tracking medical graduates longitudinally was through personal contact [32], as long as that remains possible.…”
Section: Medicinementioning
confidence: 99%
“…Studies identified a range of challenges related to classifying the geographical distribution of medical workforce, which were as follows: uptake of rural internships by domestic graduates being insufficient to meet rural workforce demands [76]; movement of graduates who were international fee-paying students to metropolitan areas after the first few years of practice [82]; and the lack of availability of specialty training in non-metropolitan areas [57]. The sensitivity of AHPRA principal place of practice data was also examined in one study, which found that the most accurate method of tracking medical graduates longitudinally was through personal contact [32], as long as that remains possible.…”
Section: Medicinementioning
confidence: 99%
“…As most specialist training (other than general practice training) is provided in metropolitan areas, many graduates remain in cities until they attain vocational qualifications. One study found that “many junior doctors — even those with a strong interest in rural practice — feel pressured to choose to train in metropolitan locations.” 16 However, serving a rural internship is associated with later rural practice 17 …”
mentioning
confidence: 99%
“…Additionally, the students' comments suggest that it may be a motivating factor for preferencing remote placement locations, which may otherwise be rarely preferenced. Research has recently identified that improved understanding of the factors impacting location preferencing for internships may influence the uptake of rural internships by junior doctors (McGrail et al, 2020). Similarly, improved understanding of the factors impacting student engagement with rural placement opportunities affects location preferencing for remote placements.…”
Section: Discussionmentioning
confidence: 99%